The effect of management characteristics on audit report readability - Mahdi Salehi; Grzegorz Zimon; Maryam Seifzadeh (Economies, 2022)
The present study investigates the relationship between management characteristics (managerial entrenchment, CEO narcissism, overconfidence, board effort, real and accrual-based earnings management) and the audit report readability of listed firms. In other words, this paper seeks to answer the question of "whether management characteristics can have a favourable effect on the audit report readability or not". The multivariate regression model is used for this study. Research hypotheses were also examined using a sample of 1004 observations on the Tehran Stock Exchange during 2012-2018 and by employing multiple regression patterns based on a panel data technique and fixed effects model. The results show a negative and significant relationship between managerial entrenchment and real and accrual-based earnings management and the audit report readability, based on the FOG index, and a positive and significant relationship between management narcissism, CEO overconfidence, and board effort and the audit report readability, based on the FOG index. Moreover, a negative and significant relationship exists between management entrenchment, CEO overconfidence, real and accrual-based earnings management, and audit report readability based on text length and Flesch indices. A positive and significant relationship was evident between CEO narcissism and board effort and audit report readability based on the same indices. Besides, research models were also examined for more confidence using other additional methods, including FE, T + 1, ABB, and GMM, which confirm the study's preliminary results. Since the present study is the first paper to investigate such a topic in the emergent markets, it provides valuable information about intrinsic and acquisitive characteristics of management for users, analysts, and legal institutions that contribute significantly to financial statement readability.
Keywords: 330; audit report readability; board effort; CEO overconfidence; managerial entrenchment; real and accrual-based earnings management